Prevalence and determinants of cessation of exclusive breastfeeding among primi-para rural Indian mothers - Mohite, Rajsinh V.; Kshirsagar, Vinayak Y.; Mohite, Vaishali R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Breast milk is first, natural and nutritious food for newborn that promote sensory and cognitive development as well as protect against infectious and chronic diseases. The aim and objective of the study was to estimate the prevalence and to point out determinants of cessation of exclusive breastfeeding among rural primi-para mothers. Methods: This is a hospital based cross sectional study conducted at rural tertiary health centre located Western Maharashtra, India in the month of November-December 2017. A total of 140 breastfeeding primi-para mothers were enrolled and interviewed by utilizing pretested questionnaire include socio-demographic data, obstetric and breastfeeding history after written consent. Data were analyzed for inferential statistics using SPSS Version 21. Results: Among 140 eligible mothers, max. 84.2% were in age group 18-24 years with high proportions, 72.8% housewives, 90% literate and 75.7% with joint family structure. Max. 92.1% mothers were institutionally delivered. The overall prevalence of cessation of exclusive breastfeeding was 22.85% with gradual and sudden cessation was 20% and 2.85% respectively. Maternal determinants like insufficient breast milk secretion (37.5%), maternal sickness (12.5%) were highly contributed for cessation of breastfeeding whereas, infant illness, 12.5% respectively. The nuclear family structure, caesarean delivery and low birth weight baby were significantly associated with cessation of exclusive breastfeeding. The risk of cessation of exclusive breastfeeding is of 4.5 and 2.5 times higher with maternal nuclear family structure and infant with low birth weight. Conclusions: Prevalence of cessation of exclusive breastfeeding was low among primi-para mothers residing in rural area of western Maharashtra, India. The nuclear family structure, low birth weight baby have had significant effect on cessation of exclusive breastfeeding.